David Copperfield - Dickens, Charles (London : Oxford University press, 2005)
The novel follows David Copperfield from his difficult childhood through his youth and into adulthood. Orphaned early and mistreated by his stepfather, David faces hardships but gradually overcomes them through perseverance, education, and friendships. Along the way, he encounters memorable characters, experiences love and loss, and learns important lessons about honesty, kindness, and resilience. Ultimately, David finds personal and professional fulfillment, reflecting Dickens$1 (Bs themes of social justice and moral growth.s